Case Report: Borrelia-DNA Revealed the Cause of Arthritis and Dermatitis During Treatment With Rituximab - Sjöwall, Johanna; Xirotagaros, Georgios; Anderson, Chris D.; Sjöwall, Christopher; Dahle, Charlotte (Frontiers in Neurology, 2021)
Borrelia-specific antibodies in serum did not contribute to the diagnosis of Borrelia arthritis or Borrelia-associated dermatitis in a young woman with ongoing treatment with rituximab due to multiple sclerosis. The diagnosis was confirmed by the detection of Borrelia-DNA in a skin punch biopsy. The patient history did not reveal any tick exposure. She had suffered for several months from fluctuating pain and swelling of the right knee as well as skin involvement with redness and oedema around the ankle of the same leg. Monoarthritis was confirmed by a rheumatologist. Knee puncture was performed but the synovial fluid was only sufficient for microscopic examination of crystals. Neither monosodium urate crystals nor calcium pyrophosphate crystals were found. Borrelia serology in blood revealed borderline levels of immunoglobulin (Ig)M and IgG, respectively. Treatment with doxycycline resulted in resolution of the joint and skin manifestations within a month. This case highlights that Borrelia-specific antibody levels cannot be reliably interpreted in patients who have received B-cell depleting therapy. Under these circumstances, detection of the bacterial genome in different body fluids, such as in the skin, can be a useful complement to the diagnosis of Lyme disease. In this young female, the diagnosis would certainly have been further delayed without the detection of Borrelia-DNA in the skin.